Integration of the Three Religions in Chinese Ideological History: Four Stages And Three Dimensions. - KHAN, KHATIB AHMAD; YANSHENG, WU; AIGERIM, DANABEKOVA (The journal of contemporary issues in business and government, 2021)
There is a very remarkable phenomenon in the Chinese ideological history which is known as ‘the integration of the three religions’. The three religions refers to Confucianism, Taoism and Buddhism. Since its introduction into China in 2nd century B.C., after a long fusion with local Confucianism and Taoism, Buddhism has finally succeeded in taking its roots in Middle Kingdom. Standing side by side with Confucianism and Taoism, It has become the mainstream of Chinese ideology and culture. During the process of fusion, the three schools of thought of Confucianism, Taoism and Buddhism have jointly formed the three cornerstones of Chinese traditional culture. Based on the fusion of Buddhism, Chinese Confucianism and Taoism, this paper explores the four stages and three dimensions of the integration of the these three religions in China.